ABI End of Initiative - 2024 Progress Deep Dive of the barley, wheat, faba bean, grasspea, kabuli chickpea, and lentil breeding teams from ICARDA - Bassi, Filippo Maria (International Crops Research Institute for the Semi-Arid Tropics, 2024)
The presentation summarizes the barley, wheat, faba bean, grass pea, kabuli chickpea, and lentil breeding teams' efforts and progress from 2022 to 2024 through a series of questions that highlight the teams' breeding achievements. It also discusses the teams' successes and challenges during this period.